Femoral Nerve Injury Complicating Surgery for Gynecologic Cancer. Issue 6 (1st July 2014) - Maneschi, Francesco; Nale, Roberta; Tozzi, Roberto; Biccirè, Desiree; Perrone, Seila; Sarno, Michele
Abstract : Objective: The aim of this study was to report the incidence, severity, and factors associated with femoral nerve injury during gynecologic cancer surgery. Methods: All patients who underwent abdominal surgery for gynecologic cancer entered the study. A retrospective review of the medical records was carried out for patients operated on from 2003 to April 2011. After this analysis, the use of the Bookwalter retractor was modified and the data were prospectively recorded. Results: In the first period, femoral nerve injury was observed in 11 (2.7%) of 406 patients, occurring with a significantly higher frequency when the Bookwalter retractor was used (5.1% vs 0%, P < 0.01) and when pelvic lymphadenectomy was performed (5.1% vs 0.9%, P < 0.01). The analysis of the 212 patients (52.2%) in the Bookwalter group showed higher frequency of nerve injury in the patients undergoing pelvic lymphadenectomy (7.8% vs 2.0%, P = 0.05). In the second period, femoral nerve injury was observed in 1 (0.7%) of 132 patients operated on and in 1 (2.3%) of 43 patients (32.6%) in the Bookwalter group. When comparing the 2 periods, the lesser use of the Bookwalter retractor and the reduced time of maximal traction of the pelvic blades decreased the nerve injury rate from 2.7% to 0.7% and, in the Bookwalter group, from 5.1% to 2.3%. These results, although not statistically significant, are clinically relevant. Conclusions: Femoral nerve injury during gynecologic cancer surgery was associated with the Bookwalter retractor. The pelvic blades of the retractor may exert a compression on the nerve. The weakened muscles suggest that the nerve compression occurred intrapelvically over the iliacus muscle. Shortening the time of maximal traction of the pelvic blades reduced the incidence of femoral nerve injury. When performing gynecologic surgery with the use of the Bookwalter retractor, care must taken with the placement of the pelvic blades.